1995
DOI: 10.1128/mcb.15.3.1169
|View full text |Cite
|
Sign up to set email alerts
|

Binding of NCK to SOS and Activation of ras-Dependent Gene Expression

Abstract: NCK, an SH2-and SH3 domain-containing protein, becomes phosphorylated and associated with tyrosine kinase receptors upon growth factor stimulation. The sequence of NCK suggests that NCK functions as a linker between receptors and a downstream signaling molecule. To determine if NCK can mediate growth factorstimulated responses, we measured the ability of NCK to activate the fos promoter. We found that in NIH 3T3 cells, NCK strongly activates this promoter. The effect of NCK on the fos promoter is enhanced by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 34 publications
1
89
0
Order By: Relevance
“…It has been reported that Nck can regulate p21ras-dependent gene transcription through interaction with SOS, an activator of Ras nucleotide exchange (Hu et al, 1995). This raised the possibility that activation of Pak1 via myristoylated Nck SH3(2) is an indirect e ect of activation of the Ras/Raf pathway due to membrane relocalization of SOS.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that Nck can regulate p21ras-dependent gene transcription through interaction with SOS, an activator of Ras nucleotide exchange (Hu et al, 1995). This raised the possibility that activation of Pak1 via myristoylated Nck SH3(2) is an indirect e ect of activation of the Ras/Raf pathway due to membrane relocalization of SOS.…”
Section: Resultsmentioning
confidence: 99%
“…In these cells, Nck did not, however, interfere with the EGFand the NGF-stimulated Ras and MAPK activation (Rockow et al, 1996). On the other hand, it has also been reported that overexpression of Nck activated the c-fos promoter in a Ras-dependent manner in NIH3T3 cells, in which a stable complex of Nck and mSos was detected (Hu et al, 1995). The reason for this discrepancy among the above independent studies remains unknown.…”
Section: Introductionmentioning
confidence: 93%
“…It has been proposed that the binding of Nck to p130 cas upon stimulation of Src 7 cells with ®bronectin might facilitate signaling to Erk2 (Schlaepfer et al, 1997). It has also been demonstrated that Nck can bind to Sos in vitro (Hu et al, 1995) potentially activating the Ras/Raf/MAPK pathway. On the other hand, PC12 cell di erentiation induced by basic FGF has been shown to be inhibited by Nck in a MAPK-independent mechanism (Rockow et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The three SH3 domains of Nck can bind to di erent downstream signaling proteins (Chou and Hanafusa, 1995;Hu et al, 1995;Kitamura et al, 1996;Lu et al, 1997;Quilliam et al, 1996;Rivero-Lezcano et al, 1994, 1995. We have previously shown that ectopic expression of Nck constructs in which both the ®rst and second SH3 domains are intact leads to ventralization and anterior truncation of Xenopus embryos (Tanaka et al, 1997).…”
Section: E Ect Of Combinations Of Dn Nck and Grb2 Adapters Upon Efgf-mentioning
confidence: 99%
See 1 more Smart Citation